"Nobody Will Tell You. You've Got to Ask!": An Examination of Patient-Provider Communication Needs and Preferences among Black and White Women with Early-Stage Breast Cancer. Issue 11 (19th September 2021) - Anderson, Janeane N.; Graff, J. Carolyn; Krukowski, Rebecca A.; Schwartzberg, Lee; Vidal, Gregory A.; Waters, Teresa M.; Paladino, Andrew J.; Jones, Tameka N.; Blue, Ryan; Kocak, Mehmet; Graetz, Ilana
ABSTRACT: Patient-provider communication is a critical component of healthcare and is associated with treatment quality and outcomes for women with breast cancer. This qualitative study examines similarities and differences in patient perspectives of communication needs between Black and White breast cancer survivors. We conducted four focus groups ( N = 28) involving women with early-stage breast cancer on adjuvant endocrine therapy (AET), stratified by race and length of time on AET (< 6 months and >6 months). Each group was moderated by a race-concordant moderator and analyzed by emergent themes. Participants expressed common patient-provider communication needs, namely increased sensitivity from oncologists during the initial cancer diagnosis, personalized information to facilitate treatment decisions, emotional support during the transition from active treatment to maintenance, and rapid provider responses to mobile app-based queries. Communication differences by race also emerged. Black women were less likely than White women to describe having their informational needs met. White women praised longstanding relationships with providers, while Black women shared personal stories of disempowered interactions and noted the importance of patient advocates. White women more often reported privacy concerns about technology use. Unlike White women, Black women reported willingness to discuss sensitive topics, both online and offline, but believed those discussions made their providers feel uncomfortable. Early-stage breast cancer patients on AET, regardless of race, have similar needs for patient-centered communication with their oncologists. However, Black women were more likely to report experiencing poorer communication with providers than White women, which may be improved by technology and advocates.